Fatal Myocarditis in Course of Plasmodium falciparum Infection: Case Report and Review of Cardiac Complications in Malaria - Paola Costenaro; Paolo Benedetti; Chiara Facchin; Carlo Mengoli; Giampietro Pellizzer (Case Reports in Medicine)
We describe a fatal case of imported malaria where the sole finding revealed at the postmortem evaluation was an acute lymphocytic myocarditis with myocardiolysis. This case recalls the potential importance of myocardial injury in the prognosis of malaria and prompts a reevaluation of current perspectives on the pathogenesis of severe falciparum infection. In the light of this, we have reviewed the cases of cardiac complications in malaria published to date.